2018
DOI: 10.1002/ijc.31640
|View full text |Cite
|
Sign up to set email alerts
|

Circulating isoflavone and lignan concentrations and prostate cancer risk: a meta‐analysis of individual participant data from seven prospective studies including 2,828 cases and 5,593 controls

Abstract: Phytoestrogens may influence prostate cancer development. This study aimed to examine the association between prediagnostic circulating concentrations of isoflavones (genistein, daidzein, equol) and lignans (enterolactone and enterodiol) and the risk of prostate cancer. Individual participant data were available from seven prospective studies (two studies from Japan with 241 cases and 503 controls and five studies from Europe with 2,828 cases and 5,593 controls). Because of the large difference in circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…When these types of food are consumed, they have multiple effects (Vitale et al, 2013). Epidemiological studies have indicated that populations with a high isoflavone intake through soy consumption have lower rates of several cancers, such as breast, prostate, bladder, gastric, and colon cancer (Kweon et al, 2013; Zhang et al, 2017; Perez-Cornago et al, 2018; Wada et al, 2018; You et al, 2018; Grainger et al, 2019). Isoflavones are considered chemoprotective and can be used as an alternative therapy for a wide range of hormonal disorders (van Duursen, 2017; Křížová et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When these types of food are consumed, they have multiple effects (Vitale et al, 2013). Epidemiological studies have indicated that populations with a high isoflavone intake through soy consumption have lower rates of several cancers, such as breast, prostate, bladder, gastric, and colon cancer (Kweon et al, 2013; Zhang et al, 2017; Perez-Cornago et al, 2018; Wada et al, 2018; You et al, 2018; Grainger et al, 2019). Isoflavones are considered chemoprotective and can be used as an alternative therapy for a wide range of hormonal disorders (van Duursen, 2017; Křížová et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavones, largely from soya foods, have been associated with a reduced risk for prostate cancer in Asian men,77 and plasma concentrations of the isoflavone equol might be inversely associated with prostate cancer risk in men in Japan 78…”
Section: Prostate Cancermentioning
confidence: 99%
“…While the results obtained from two population-based case-control studies on diet, inherited susceptibility and PCa support the idea that a phytoestrogen-enriched diet may protect against the tumor in Scottish and Sicilian men [297,298], in a European Prospective Investigation into Cancer and Nutrition study genistein concentrations in the plasma samples of 1605 PCa cases and 1697 matched control participants were not correlated with cancer risk [299]. Globally, a recent meta-analysis of single patient data from seven prospective studies (two Japanese studies with 241 cases and 503 controls and five European studies with 2828 cases and 5593 controls) did not show any significant correlation between prediagnostic intake of isoflavones and PCa development, although further studies should be performed in populations where isoflavone intakes are high [300]. In this respect, it should be underlined that purified genistein have been demonstrated to be well tolerated in 20 PCa patients treated with 300 or 600 mg isoflavone/day for 84 days, showing no genotoxicity [301] and causing only minor estrogenic effects, such as hot flashes and breast changes [302].…”
Section: Clinical Impactmentioning
confidence: 95%